Towards Visualizing Educational Block-Based Scratch Code With the City Metaphor - Robles, Gregorio; Escobar-Morales, Daniel; Montes-Leon, Sergio; Moreno-Leon, Jesus; Pons-Castro, Guillermo; Moreno-Lumbreras, David (Proceedings of VISSOFT (Online), 2025)
The Code City metaphor stands as a prominent and widely recognized technique for visualizing software projects. This paper explores the application of the Code City metaphor within the context of Scratch, the most prevalent block-based programming language employed in educational settings. By leveraging the Code City metaphor and its implementation in BabiaXR, we have developed a prototype that renders Scratch projects in a visually intuitive urban landscape. We posit that the integration of the Code City metaphor with Scratch projects holds significant potential for enhancing learning environments by providing novel perspectives on project structure and potential areas for improvement.